Compositional study of the lost temples in instructional design - Kozlova, Galina; Kozlova, Lyudmila (project baikal, 2021)
The article presents the design and research work of the authors and first-year architecture students of Irkutsk National Research Technical University concerning compositional study of lost temples of Irkutsk with the reconstruction of their architectural appearance. The illustrative material was prepared using the students’ works. The complex of Siberian Baroque temples in Irkutsk in the mid-18th – late 19th centuries and various types of church buildings were studied. The work uses modeling as a tool for predicting the architectural appearance of the temple. Sketch drawings and models of the Miracle-Working, Tikhvinsky and Annunciation temples were completed, and the model of the evolution of Siberian Baroque temples was recreated. The main stages of the term project, from building functional, planning and volumetric models to designing image and structural characteristics of the object on the sample board, were presented.
Keywords: lost architectural heritage; temple ensemble; evolutionary development; Siberian Baroque; compositional modeling